2008
DOI: 10.1590/s0034-89102008005000021
|View full text |Cite
|
Sign up to set email alerts
|

Significados culturais da asma infantil

Abstract: OBJECTIVE:To analyze the cultural meanings of infantile asthma from the perspective of the mother/carer of the child. METHODOLOGICAL PROCEDURES:Qualitative research conducted in 2004, in the city of Fortaleza (Northeastern Brazil). An ethnographic approach was utilized, consisting of participant observation and interviews with seven mothers, accompanying their children in a hospital emergency ward. Thematic analysis was the technique employed when identifying the meanings of mothers' discourse. ANALYSIS OF RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…The mothers’ reports of asthma symptoms may be imprecise, given their erroneous interpretations of perceptions of these symptoms, as well as problems understanding questions, particularly when we consider that this population has a low socioeconomic status. Difficulties reported by the mothers in understanding the term “wheezing,” as used in the ISAAC questionnaire, have already been reported ( Frota, Martins, & Santos, 2008 ).…”
Section: Discussionmentioning
confidence: 96%
“…The mothers’ reports of asthma symptoms may be imprecise, given their erroneous interpretations of perceptions of these symptoms, as well as problems understanding questions, particularly when we consider that this population has a low socioeconomic status. Difficulties reported by the mothers in understanding the term “wheezing,” as used in the ISAAC questionnaire, have already been reported ( Frota, Martins, & Santos, 2008 ).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, other authors found that children complained of fever of various origins, such as infections of the upper and lower airways, among others (14) . Just as a study of a systematic review on the inappropriate use of emergency services corroborates to the result, saying the majority of complaints accounted for fever (21.6%), followed by vomiting (18.1%) (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Muitos fatores contribuem para isso, tais como os componentes culturais, que influenciam no processo de aquisição das medidas corretas para prevenção da doença. Assim, no intuito de melhorar a qualidade no cuidado ao outro (11) , é importante os profissionais reconhecerem e identificarem as implicações dos fatores socioculturais no processo saúde--doença, buscando ampliar o foco do cuidado para além da dimensão biológica do indivíduo.…”
Section: Discussionunclassified